How does climate exacerbate root causes of conflict in Senegal? Climate Security Pathway Analysis - Madurga Lopez, Ignacio M.; Medina, Leonardo; Carneiro, Bia; Liebig, Theresa Ines; Läderach, Peter R.D.; Pacillo, Grazia (2023)
This factsheet gives answers on how climate exacerbates root causes of conflict in Senegal, using an impact pathway analysis. Two main impact pathways are identified: 1) Livelihood and food insecurity in Matam and Tambacounda; 2) Fish scarcity, livelihood insecurity and recruitment by NSAGs.